Antiangiogenic Phytochemicals Constituent of Diet as Promising Candidates for Chemoprevention of Cancer - Ana Dácil Marrero; Ana R. Quesada; Beatriz Martínez-Poveda; Miguel Ángel Medina (MDPI AG, 2022)
Despite the extensive knowledge on cancer nature acquired over the last years, the high incidence of this disease evidences a need for new approaches that complement the clinical intervention of tumors. Interestingly, many types of cancer are closely related to dietary habits associated with the Western lifestyle, such as low fruit and vegetable intake. Recent advances around the old-conceived term of chemoprevention highlight the important role of phytochemicals as good candidates for the prevention or treatment of cancer. The potential to inhibit angiogenesis exhibited by many natural compounds constituent of plant foods makes them especially interesting for their use as chemopreventive agents. Here, we review the antitumoral potential, with a focus on the antiangiogenic effects, of phenolic and polyphenolic compounds, such as quercetin or myricetin; terpenoids, such as ursolic acid or kahweol; and anthraquinones from Aloe vera, in different in vitro and in vivo assays, and the available clinical data. Although clinical trials have failed to assess the preventive role of many of these compounds, encouraging preclinical data support the efficacy of phytochemicals constituent of diet in the prevention and treatment of cancer, but a deeper understanding of their mechanisms of action and better designed clinical trials are urgently needed.